Science-policy communication for improved water resources management: Contributions of the Nostrum-DSS project - Yaella Depietri; Carlo Giupponi (Fondazione Eni Enrico Mattei (FEEM), 2008)
The Nostrum-DSS EU funded Co-ordination Action (CA) aims at contributing to the achievement of improved governance and planning in the field of sustainable water management within the Mediterranean Basin by establishing a network between the science, policy, and civil society spheres and through the development and dissemination of Best Practices Guidelines (BPGs) for the design and implementation of DSSs for IWRM in the Mediterranean Area. Decision Support Systems (DSS) have a great theoretical potential as tools for the identification of optimal water resource management regimes in the Mediterranean basin, thus helping policy makers (PMs) to bring the principles of Integrated Water Resources Management (IWRM) into practice. However, such tools are only episodically exploited outside the academia. This article presents the outcomes of project activities targeting the development of more effective communication strategies, in order to facilitate the development of research products with greater potential for been up taken by the expected end-users, i.e. the community of policy makers, and their staffs, advisors, consultants, etc., in the Mediterranean Region.
Keywords: Q2; H7; O2; R5; 330; Science-Policy Interface; Policy Making; Water Resources Management; Mediterranean Region; Wasserversorgung; Wasserpolitik; Ressourcenökonomik; Internationale Umweltpolitik; Mittelmeerraum